Phytochemical and biological activities of Alpinia mutica, Beosenbergia armeniaca (Zingiberaceae) and Aglaia variisquama (Meliaceae) - Mustahil, Noorul Adawiyah (2014)
Phytochemical study on the rhizomes of Alpinia mutica afforded four compounds; a kavalactone, 5,6-dehydrokawain (6) as a major constituent and the flavonoids; flavokawin B (12), pinostrobin (33) and pinocembrin (9) together with β-sitosterol (14) while, isolation work on the rhizome extracts of Boesenbergia armeniaca afforded two pyrone compounds; 6-aryl-4-methoxy-2-pyrone (93) and 6-cis-styryl-4-methoxy-2-pyrone (94). Compounds (93) and (94) were new to the species and this is a first report on their structural elucidation using 2D NMR spectroscopy. Similar work on the leaves of Aglaia variisquama yielded two triterpene compounds; lupenone (95) and lupeol (96) together with β-sitosterol (14) and this is a first report on phytochemicals of the leaves of A. variisquama. The crude hexane and chloroform extracts of the rhizomes of A. mutica showed significant cytotoxicity against HT-29 (human colon) cancer cells with IC50 values less than 15 μg/mL. The crude hexane extract also showed significant cytotoxic activity against MCF-7 (human breast) cancer cells with an IC50 value of 16.10 μg/mL. Flavokawin B (12) was the most cytotoxic constituent against HT-29 and MCF-7 cancer cells with an IC50 value of 4.68 μg/mL and 5.18 μg/mL, respectively. Besides, compounds (6), (33) and (9) also showed significant cytotoxicity against HT-29 and MCF-7 cancer cells with an IC50 value ranging from 6 to 13 μg/mL, except for pinocembrin (9) which exhibited weak cytotoxicity against MCF-7 cancer cells. The cytotoxicity of the isolates of the rhizomes of A. mutica against human cancer cell lines using MTT assay is firstly reported here. All the rhizome extracts of B. armeniaca demonstrated significant cytotoxicity against HeLa (human cervical) cancer cells with an IC50 value ranging from 16 to 18 μg/mL, except for the methanol extract which was inactive. The crude ethyl acetate extract was the most cytotoxic against MCF-7 cancer cells with an IC50 value of 1.10 μg/mL. Moreover, compounds (93) and (94) showed significant cytotoxicity against MCF-7 cancer cells with an IC50 value of 16.70 μg/mL and 14.10 μg/mL, respectively. All the crude extracts of the leaves of A. variisquama showed significant cytotoxicity against HeLa cancer cells with IC50 values less than 15 μg/mL while, its methanol extract exhibited weak cytotoxicity. Here, the cytotoxic activities of compounds (93) and (94) as well as the crude extracts of the leaves of A. variisquama against human cancer cells are firstly reported.